A systematic bioinformatics approach for selection of target and screening of ligand for malignant tumours suppressing APG4A gene on Xq22.1. (7th February 2011) - Niranjan, Vidya; Seenivasagam, R.; Sivakumar, G.
Autophagy is a biological process involved in the intracellular destruction of endogenous proteins and has been suggested to be essential for cell homeostasis as well as for cell remodelling. Autophagy selectively eradicates damaged cytoplasmic components like injured mitochondria, which increases mutation rates and promote tumour initiation and progression. In addition, autophagy inhibits necrosis, which promotes progression by inducing angiogenesis and metastasis. This study aims to find autophagy-related cysteine endopeptidase A (APG4A) which has a significant role in suppressing various cancers. This bioinformatics research with a suitable target for inducing autophagy through APG4A would be a real breakthrough in cancer therapy.